Kajian hubungan prestasi akademik dengan aktiviti kawad kaki pengakap serta koheren heart rate variability (hrv) di kalangan pelajar sekolah rendah - Zulli, Muhamad (2021)
Student excellence is measured in terms of academic achievement as well as co curriculum. Scouting is a co-curricular activity that is believed to have succeeded in producing students who excel in academics and discipline. The main activity of scouts is foot marching. Studies also show that excellent students also have good coherent HRV scores. The HRV coherent score indicates the individual's ability to control the mind and heart simultaneously and this is also a criterion for student excellence. The purpose of this study is to identify the relationship between academic achievement and marching performance among primary school students, examine the effect of marching training on HRV coherence score, analyze students' academic achievement and their ability to control HRV coherence, and examine the extent to which marching training can help students improve HRV achievement and academic achievement. The study sample was taken from rural primary school students in Felda Lepar Hilir 3, Kuantan who underwent scout foot training. Data collection methods using academic achievement results, observation of student foot marching training performance and the use of biofeedback tools for measuring coherent HRV scores among samples. The study also used quasi experimental techniques between control and training groups to examine the effects of foot marching training on students. The findings of the study show that good students with academic achievement are those who have good marching ability. Findings show that foot marching training is not able to imp rove the coherent HRV score of students with good academic achievement and also weak. There are no obvious differences in coherent scores according to differences in academic achievement. The findings of the study showed that students with good academic ac hievement were not able to control the coherent score of HRV after the marching exercise was carried out in the same situation as students with poor academic achievement. The student's LF spectrum reading score was higher after the foot march than before the parade exercise was performed. The findings also show that the five-day foot march training is not able to help students improve their HRV score as well as their academic achievement. The findings show that there is no difference in the average score of academic achievement and HRV coherent score between good and weak students after going through foot marching training either for LF and VLF spectrum. The findings of this study show that foot marching training is not able to help students to improve the coherent score of HRV whether students are good or weak. The findings also show that marching exercises are not able to help students improve their academic achievement after foot marching training is given. The overall findings of the study conclude that scout foot marching exercises performed by primary school students will increase their level of emotional stress with decreased LF spectrum score. This shows that this exercise is not able to help students to improve their cognitive performance. The results of this study conclude that foot marching training needs to be re-evaluated to enable it to help reduce students' emotional stress and also to help students improve their level of self-control and academic achievement. Empowerment of foot marching training will increase student involvement in co-curricular activities that contribute to the development of excellent students.